A Systems Biology Perspective on Rational Design of Peptide Vaccine Against Virus Infections - Chen, Jiajia; Wang, Ying; Guo, Deyin; Shen, Bairong (Current Topics in Medicinal Chemistry, 2012)
With the recent onset of influenza A (H1N1) pandemic, the need for improved vaccines against virus infections has become an international priority. Strategies for vaccine development have changed over time, from whole-virus to immunogenic proteins and further to antigenic viral peptides. Various algorithms and bioinformatics tools have been developed to predict immunogenic peptide regions in an antigenic protein sequence. Recent advances in next-generation sequencing technologies, as represented by real time DNA sequencing, provide increased throughput and yield of data on viral pathogens and host cells. This enables us to ‘mine’ the genomic sequence for putative vaccine candidates or targets, allowing a more rational approach to the peptide vaccine design. This review first describes current computational tools available for the rational design of peptide vaccines and then addresses recent attempts to define pathogenic peptides at ‘- omics’ level. As there are interplay between antibody and T cells, as well as intersection between viruses and hosts, the vaccine-mediated immunity are orchestrated by multiple factors within an interaction network. Therefore, single viral peptide alone fails to provide optimal immunity. Systems biology offers a systems-level perspective of how the various arms of the immune response are integrated to give immune response, as well as how host and virus interact, thereby providing an integrated approach to select the most promising candidates for peptide vaccines development. We highlight in this article the system-level application of rational peptide vaccine design, which may be a general paradigm for future viral vaccine development.
Keywords: omics